2018
DOI: 10.3390/toxins10110451
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Breast Cancer Activity of Latroeggtoxin-V Mined from the Transcriptome of Spider Latrodectus tredecimguttatus Eggs

Abstract: As a black widow spider, Latrodectus tredecimguttatus has poisonous components not only in venomous glands but also in eggs. Our previous work had carried out a transcriptome analysis of the spider eggs in an attempt to probe into the molecular basis of the egg toxicity. A proteinaceous toxin, named Latroeggtoxin-V, was mined from the identified transcriptome. In this study, the gene of Latroeggtoxin-V was cloned and heterologously expressed, and the anticancer activity of the recombinant Latroeggtoxin-V (rLat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…To date, many anticancer peptides have been screened from animal venom. For example, the spider polypeptide latroeggtoxin-V inhibits the proliferation, migration, and cell cycle of breast cancer MDA-MB-231 cells in a concentration-dependent manner ( Xu et al, 2018 ). Melittin, the main peptide component of Apis mellifera venom, inhibits EGF-induced cell movement and invasion by inhibiting the PI3K/Akt/mTOR signalling pathway in breast cancer cells ( Lim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, many anticancer peptides have been screened from animal venom. For example, the spider polypeptide latroeggtoxin-V inhibits the proliferation, migration, and cell cycle of breast cancer MDA-MB-231 cells in a concentration-dependent manner ( Xu et al, 2018 ). Melittin, the main peptide component of Apis mellifera venom, inhibits EGF-induced cell movement and invasion by inhibiting the PI3K/Akt/mTOR signalling pathway in breast cancer cells ( Lim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few articles analyzed the antitumor action of components from widow spiders' venom and eggs. The recombinant latroeggtoxin-V inhibits the proliferation and migration of breast cancer cells (MDA-MB-231) and also causes their apoptosis; the toxin inhibits the activity of the Na + /K + -ATPase in a concentration-dependent manner, suggesting that its action affects ion transport [218].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…In the transcriptome analysis of the L.tredecimguttatus eggs, Xu et al found a series of genes that encode proteinaceous toxins, two of which were named latroeggtoxin‐V and latroeggtoxin‐VI, respectively (Xu and Wang 2016). Latroeggtoxin‐V was shown to selectively inhibit breast cancer cell lines MDA‐MB‐231 by affecting the activity of Na + /K + ‐ATPase (Xu et al 2018) Latroeggtoxin‐VI (LETX‐VI) can increase the levels of total and released dopamine in PC12 cells, which is influenced by extracellular Ca 2+ and, however, the exact underlying molecular mechanism has not been fully clear (Tang et al 2021a).…”
Section: Introductionmentioning
confidence: 99%